1991
DOI: 10.1007/bf02049970
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic removal of a large colonic lipoma

Abstract: A 72-year-old white male was found to have a 6-cm submucosal mass at 35 cm on screening sigmoidoscopy. The lesion had all the characteristics of a submucosal lipoma. Instead of performing a laparotomy with its potential morbidity, the lesion was removed laparoscopically in its entirety without untoward operative sequelae. Laparoscopic techniques have had a profound impact on the treatment of patients with surgical disorders. This new technology can be applied to selected patients with colorectal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…During the initial years, major 1.5 >200 0.8 assessment was focused upon the feasibility and technique of these operations [4,11,17,24,25,30]. Much information was generated regarding port placement, instrumentation, personal preferences, and early results.…”
Section: Discussionmentioning
confidence: 99%
“…During the initial years, major 1.5 >200 0.8 assessment was focused upon the feasibility and technique of these operations [4,11,17,24,25,30]. Much information was generated regarding port placement, instrumentation, personal preferences, and early results.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no prospective randomized trial has been reported. The first reports of the application of laparoscopic surgery to colon resection were in 1991 [5,12,13,15,18,22,23]. Redwine and Sharpe detailed the transanal extraction of an endometrioma of the sigmoid colon with a stapled end-to-end anastomosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Redwine and Sharpe detailed the transanal extraction of an endometrioma of the sigmoid colon with a stapled end-to-end anastomosis [20]. Nezhat et al [18], Saclarides et al [22], Lange et al [13], and Schlinkert [23] also reported their technique and experience of one procedure during 1991. Jacobs and his colleagues published the first series of 20 patients undergoing laparoscopically assisted colectomy with a detailed description of the technique [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although laparoscopic techniques were first applied to colorectal surgery in 1991, [3][4][5][6] the approach has not been widely adopted. This is largely because of concerns over the safety of these techniques in cancer surgery.…”
Section: Resultsmentioning
confidence: 99%